Factores que influyen en la presencia de anemia en embarazadas que acuden al Sub Centro De Salud 27 de Febrero de la Ciudad de Macas. Año 2015 - Chacha Chucay, Rubí Alexandra (2016)
The present study was performed in order to identify the factors that influence the presence of anemia in pregnant women attending the Sub Health Center on February 27 in the city of Macas. The research design was cross-sectional, descriptive, and bibliographic and field, using as observation and survey techniques for the actual information. The following results were obtained: Mainly pregnant adolescents 15-19 years of age with 44%, followed by 20-29 years in 40%, 52% mixed ethnicity. Concerning marital status 36% are single mothers and 28% are divorced, from rural 56, prevailing secondary level study with 52%. Regarding occupation 32% work in agriculture, 24% housework. The prevalence of anemia in pregnant women is 29.42%, 80 % with hemoglobin level of 10.1 - 11g / dl mild anemia, manifesting itself in the second trimester with 44%. Regarding the factors influencing the anemia in pregnant hipermenorrea were evidenced 56%, multiparity 3 to 4 pregnancies with 40% , 60% have made 2 to 4 antenatal the no prenatal care; 64% did not ingest micronutrients month, of which 56% eat 3 times a day, 40% consume carbohydrates and lipids 28%. It was concluded that the main factors influencing anemia and no prenatal care, inadequate nutrition, micronutrient deficiency and menorrhagia consumption. The author conducted educational activities Sub Health Center, and craft workshop, nutrition and home in the homes of pregnant visits, prevention manual, banner, triptychs and diptychs was developed Keywords: Factors affecting, Anemia, Pregnant